Em torno de Michel Foucault e Luis Buñuel: saber e poder na análise de O Discreto Charme da Burguesia - Motta, Priscila Canova (Universidade Federal de São Carlos, 2014)
The objective of this research is to analyze the film The Discreet Charm of the Bourgeoisie by Luis Buñuel (1972), by means of some concepts of the theoretical and methodological framework of Michel Foucault: "knowing" and "discursive statement" in its relations with the "power "and" truth ", and seek to understand the power in your workout in the film, and not only in its effects. Starting with some basics about "knowing" in Foucault, we mapped one filmic statement which appeared in some sequences, which is: "The noise that hides the discrete violence of the bourgeoisie." Therefore, we assess the "power and truth," these notions that became persistently present in the materiality of the film, prompting analysis mechanisms. Then conducted reflections on these principles by theory arqueogenealógica Foucault, then apply them to the analysis of the film. The research also presents aspects of the life of Luis Buñuel, traces relations between the military dictatorship of this movie and the Brazilian military dictatorship, and punctuate the experience of the director with the Surrealist movement his Catholic creation and exile in Spain in time of dictatorship. Buñuel all this shows in his work. We also established prior to analysis, a dialogue between Marx and Foucault in relation to the issue of power in relation to understanding the "bourgeoisie."
Keywords: Análise do discurso; Foucault, Paul-Michel, 1926-1984; Portolés, Luis Buñuel, 1900-1983; Saber; Enunciado; Verdade; Michel Foucault; Knowledge and utterance; Power; Truth; Luis Buñuel; Film; Bourgeoisie; OUTROS